KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KEMAMPUAN PROFESIONAL GURU DI SMA NEGERI 1 SANGGAU - Supriadi Supriadi; Usman Radiana; M. Chiar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research is: (1) Knowing planning competence; (2) Implementation of  competence; (3) and  competency evaluation principals SMA Negeri 1 Sanggau to improving the professionalism of teachers. This research was conducted using qualitative descriptive approach. Which is the principal as subject, as for the informant is the deputy principal and teachers. The techniques of data collection using : (1) observation; (2) interviews; and (3) documentation. Data have been collected followed by examination of the validity of data, using triangulation, with the verification and checking on the adequacy of reference. While technique of data analysis using an interactive model. The results of this research are : (1) Planning  that is done by the SMA Negeri 1 Sanggau principal include : (a) planning based on vision, mission, the purpose of schools and the needs of ( need assessment ); (b) involve all elements of the school it broadcasts; (c) perform new temporary teachers (GTT) recruitment and perform analysis of job position; (d) which it is carried out in a working meeting. (2) The implementation  in improving the professionalism of teachers is done by SMA Negeri 1 Sanggau principal : (a) to join in the training; seminar, and workshop; (b) revitalization of MGMP; (c) adding supporting facilities. (3) The evaluation is done by the principal of SMA Negeri 1  Sanggau covers : (a) perform supervision both personal and group; (b) techniques used is directly and indirectly; (c) the aspects of the assessment in supervision is pupils teachers, teacher performance in schools, the development of students, RPP, and Syllabus; (d) using format SKP. Keywords : Managerial Competence, The Professional of Teachers.